Local Speech of Elementary Students from Vranje and Serbian Language Grammar Teaching - Dragana V. Stanković (University of Belgrade, Teacher Education Faculty, 2022)
Creative, modern teaching of Serbian language actualizes the issue of the place of local speech of students in grammar teaching. When adopting a language standard, it is necessary to start from the local speech of the students and compare these two language idioms. Accordingly, the subject of this paper is the local speech of elementary school students from Vranje in teaching Serbian grammar. The aim of this paper is to determine the degree of presence of certain linguistic traits in dialect form in the speech of students and their representation in the Serbian language curricula (grammar teaching) for elementary school. For the purpose of this paper we determined the frequency of using dialect forms of certain linguistic traits by calculating the frequency index, in accordance with the methodology of sociolinguistic studies, and then we analyzed the Serbian language curricula. The obtained results show which linguistic traits do not cause major problems in adoption, which has to be taken into account in Serbian language teaching process. According to the obtained results, possible directions of curriculum innovation are indicated in line with the speaking habits of students from Vranje. The analytical framework proposed in this paper offers a model of students' local speech research, which could be applied in some further extensive research of student speech in the wider area of Prizren-Timok speech area. The research following this model could contribute to the innovation of the Serbian language curricula in elementary school and their adaptation to the Prizren-Timok speaking area.